Voltage drop-based fault attacks on FPGAs using valid bitstreams - Gnad, Dennis R. E.; Oboril, Fabian; Tahoori, Mehdi B. (International Conference on Field-programmable Logic and Applications, 2017)
Due to the widespread use of FPGAs in many critical application domains, their security is of high concern. In recent systems, such as FPGAs in the Cloud or in Systems-on-Chip (SoCs), users can gain access, even remotely, to the reconfigurable fabric to implement custom accelerators. This access can expose new security vulnerabilities in the entire system through malicious use of the FPGA fabric. In the past, attacks on the power supply level required local access to the hardware. In this paper, we reveal a security vulnerability in FPGAs that allows a valid configuration to generate severe voltage fluctuations, which crashes the FPGA within a few microseconds. Moreover, the extent of this crash is so severe, that manual power-cycling is required to be able to access and use the system again. This vulnerability has been systematically exploited in two different generations of FPGAs, and a SoC containing an FPGA. Because this vulnerability can lead to severe security attacks in systems using FPGA-based accelerators, we also analyze its underlying mechanism, and discuss possibilities for mitigation.